En bloc release of MVB‐like small extracellular vesicle clusters by colorectal carcinoma cells. Issue 1 (8th April 2019) - Valcz, Gábor; Buzás, Edit I.; Kittel, Ágnes; Krenács, Tibor; Visnovitz, Tamás; Spisák, Sándor; Török, György; Homolya, László; Zsigrai, Sára; Kiszler, Gábor; Antalffy, Géza; Pálóczi, Krisztina; et al.
ABSTRACT: Small extracellular vesicles (EVs) are membrane enclosed structures that are usually released from cells upon exocytosis of multivesicular bodies (MVBs) as a collection of separate, free EVs. In this study, we analysed paraffin embedded sections of archived human colorectal cancer samples. We studied 3D reconstructions of confocal microscopic images complemented by HyVolution and STED imaging. Unexpectedly, we found evidence that large, MVB‐like aggregates of ALIX/CD63 positive EV clusters were released en bloc by migrating tumour cells. These structures were often captured with partial or complete extra‐cytoplasmic localization at the interface of the plasma membrane of the tumour cell and the stroma. Their diameter ranged between 0.62 and 1.94 μm (mean±S.D.: 1.17 ± 0.34 μm). High‐resolution 3D reconstruction showed that these extracellular MVB‐like EV clusters were composed of distinguishable internal particles of small EV size (mean±S.D.: 128.96 ± 16.73 nm). In vitro, HT29 colorectal cancer cells also showed the release of similar structures as confirmed by immunohistochemistry and immune electron microscopy. Our results provide evidence for an en bloc transmission of MVB‐like EV clusters through the plasma membrane. Immunofluorescent‐based detection of the MVB like small EV clusters in archived pathological samples may represent a novel and unique opportunity which enables analysis of EV release in situ in human tissues.